Mildred S. Dresselhaus (1930–2017). (18th July 2017) - Jorio, Ado
Abstract : This paper is an obituary in honor to Professor Mildred S. Dresselhaus, who passed away on 20 February 2017, letting behind a memorable contribution to the field of Raman spectroscopy applied to carbon materials. With 8 figures and 60 selected references, this text shortly overviews her contribution on paving the basis of our knowledge on graphite, graphite intercalated compounds, graphite ion‐implantation, graphite fibers, fullerenes, carbon nanotubes, and two‐dimensional systems, starting from graphene. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : Raman spectroscopy lost one of its greatest contributors, Mildred S. Dresselhaus. She co‐authored about 350 papers carrying the word 'Raman' in the title. She had significant contribution to pave the field of Raman spectroscopy applied to graphene‐related materials: (1970s) graphite and graphite intercalated compounds, (1980s) graphite ion‐implantation and fibers, (1990s) fullerenes, (2000s) carbon nanotubes, and (2010s) two‐dimensional systems.